The effectiveness of virtual reality media on student learning outcomes: A meta-analysis - Setiawan, Risky; Yuliantri, Rhoma Dwi Aria; Aman, Aman; Fitri, Ebtana Sella Mayang; Kurniawati, Indri; Ramadan, Syahri; Huda, Nurul; Elyana, Luluk (Graduate School, Universitas Negeri Yogyakarta, 2024)
This study aims to analyze the effect of virtual reality media on student learning outcomes seen from the value of the effect size of published studies. This study used the meta-analysis method, with a group contrast design from experimental research and quasi-experiments that had experimental groups and control groups. The database used is the SCOPUS database. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method determines articles. Data collection is carried out by collecting article metadata with specific keywords that have been determined. The article metadata obtained is then sorted based on inclusion and exclusion criteria. The next step is to download a PDF of the article that matches the criteria. The downloaded PDF is tabulated to obtain statistical data in effect size calculations. Calculation of the effect size of each study and data analysis to prove research hypotheses using the R application version 4.2.0 and assisted by the RStudio. The results showed a Q value of 163.54 with a p-value of 0.0001 < Î± (0.05), so it can be concluded that there is heterogeneity from the observed data regarding the effectiveness of virtual reality media research on learning outcomes. An I2 value of 90.8% indicates substantial heterogeneity categories. For this reason, a random effect size model is used; The results showed a random effect size of 0.6285 with a p-value of 0.0001 < Î± (0.05). A value of 0.6285 indicates the influence is in the medium category; The results showed that there were differences in the effectiveness of the given continental differences (Q value = 8.24 and p-value 0.02 > Î± (0.05)). There was no significant difference in the effectiveness of virtual reality media on learning outcomes in terms of education level (Q = 7.39 and p-value 0.02 < Î± (0.05)); The results showed that the distribution of data showed symmetric, indicating that none of the studies were distorted or article bias occurred.